Integrated Test Model on Professional Certification Through Outcome-Based Education Implementation - Sukatiman, Sukatiman; Budiwan, Jauhan; Waluyo, Waluyo (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
In contrast to previous research, the professional competency test of building engineering expert schemes offer blended integration assessment through the application of media mockup and ICT devices that are appropriate to the industry so that the assessment plays an active role in solving the problems to achieve the Outcome-Based Education (OBE) characteristics. The research purpose is to implement integration tests in the cognitive domain, and skills domain of the student end semester university to reach competence according to the Indonesian Standard of Professional Certification (BNSP). The research uses a mixed method, consisting of descriptive quantitative to analyze the data collection before and after the implementation model integration test, and qualitative to have deeper findings of research. The result of the competency test for understanding the planning guidelines in reinforced concrete structures (SNI) after using the mockup media showed that the participants were 16 assesses, were 8 students in the competent category, 7 students were included in the good competent category, and 1 student was included in the excellent competent. This research concluded that All of the assessees passed the competence level on their national professional certification competence (BNSP).